Micelles, foam containing micelles, preparation method and application
By preparing a supercritical CO2 foam system that combines self-assembled worm-like micelles with nano-silicon dioxide, the problem of poor stability of CO2 foam is solved, efficient integration of fracturing and displacement is achieved, significantly improving oil recovery and reducing costs.
Patent Information
- Application Number
- CN202411765279.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-04
- Publication Date
- 2025-02-28
AI Technical Summary
The existing CO2 foam has defects in stability and is difficult to continue to be used as an effective displacer after fracturing operations.
By accurately adjusting the ratio of surfactant to counterion, a self-assembled worm-like micelle is prepared and combined with nanosilicon dioxide and supercritical CO2 to form a stable foam system.
The high stability and oil displacement efficiency of the foam system are achieved, which can significantly improve recovery rate at high temperatures, simplify operation steps, and reduce costs.
Smart Images

Figure SMS_4 
Figure SMS_5 
Figure SMS_6
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of petroleum extraction and relates to micelles and foam containing the micelles, as well as a preparation method and application. Background Art
[0002] In the field of oil extraction, improving oil recovery is always the core goal, and displacement technology is the key means to achieve this goal. [1] . Although traditional fracturing technology has played a certain role in increasing the flow path of oil and gas, the application effect of this method in low permeability reservoirs is not ideal, and it is often accompanied by high costs and environmental pollution risks. Therefore, the industry has begun to seek more efficient and environmentally friendly alternatives, especially in foam displacement technology. Foam displacement technology has attracted attention for its significant potential in improving reservoir recovery. This technology uses surfactant-stabilized foam to displace crude oil in the reservoir. By forming a high-viscosity foam fluid, it can effectively improve oil recovery by expanding the swept volume and inhibiting gas channeling. It can also reduce operating costs and is environmentally friendly. [2-3] .
[0003] The supercritical CO2 foam displacement technology is particularly eye-catching. It uses the characteristics of supercritical CO2 to form a stable foam system to achieve a more efficient oil recovery effect. [4-5] .
[0004] Supercritical CO2 has unique physical properties such as low viscosity, high diffusivity and high solvency, which allows it to more effectively displace crude oil in reservoirs while reducing problems such as water lock, emulsification problems, formation compaction, chemical carryover and bacterial growth. [4-6] , reducing damage to the reservoir. The low viscosity of supercritical CO2 helps it flow in the pores of the reservoir, while its high diffusivity allows it to penetrate into the crude oil more easily, increasing the fluidity of the crude oil. In addition, the high solubility of supercritical CO2 helps dissolve the light components in the crude oil, reducing the viscosity of the crude oil, thereby improving the flowability and recovery rate of the crude oil. [7-8] .
[0005] In a recent study, Chen Haiyong and his team used advanced pressure diagnostic technology to comprehensively evaluate the effectiveness of CO2 foam fracturing fluid in deep coal-rock gas development. The study found that compared with traditional fracturing fluid, CO2 foam fracturing fluid has significant advantages in reducing the pump stop pressure drop rate and enhancing formation permeability, which is of great significance for improving the efficiency of coal-rock gas extraction. [9]. However, the limitations of traditional CO2 foam fracturing fluid in terms of stability make it difficult to continue to use it as an effective displacement agent after fracturing operations. At the same time, Xiaoqin Cao et al. developed a self-assembled worm-like micelle system with excellent rheological properties. The system is carefully formulated with the surfactant docosyltrimethylammonium chloride (DCTAC) and the counterion SHNC in a molar ratio of 2:1, and exhibits excellent thermal stability and high viscosity properties in environments up to 130°C, making it an ideal candidate for clean fracturing fluids in deep oil and gas reservoirs.
[10] However, the high viscosity and high interfacial tension of this system make it unsuitable for foam fracturing fluid and subsequent displacement processes.
[0006] Therefore, how to provide a CO2 foam with good stability is a technical problem that needs to be solved urgently in this field.
[0007] References:
[0008] [1] Wang Jinyu. Development and application of advanced oil recovery technology for oil field tertiary oil recovery[J]. China Chemical Trade, 2015, 320: 320-320.
[0009] [2] Li Zhaomin, Xu Zhengxiao, Li Binfei, et al. Research and application progress of foam flooding technology[J]. Journal of China University of Petroleum (Natural Science Edition), 2019, 43(5): 118-127.
[0010] [3] Li Xiaofeng, Peng Bo, Liu Qi, Jia Jihui. Research progress of microfoam flooding to enhance oil recovery[J]. Petroleum Geology and Recovery Efficiency, 2022, 29(4): 91-100.
[0011] [4] Du Dongxing, Zheng Lichen, Zhang Xu, Sun Guolong, Li Yingge, Chao Kun. Comparative experimental study on the characteristics of supercritical CO2 fluid and foam flooding in porous media[J]. Journal of Chemical Industry and Engineering, 2018, 69(S1): 58-63.
[0012] [5] Wang Guanhua. Research on supercritical CO2 foam flooding technology[D]. China University of Petroleum (East China), 2010.
[0013] [6] Li Weitao, Li Zongyang, Zhang Dong, Zhang Chuanbao, Li Youquan. Highly stable supercritical CO2 foam blocking system with zwitterionic surfactants and nanoparticles as foaming agents[J]. Oilfield Chemistry, 2024, 41(1): 101-107.
[0014] [7] Tan JT, Wang ZH, Chen SD, Hu H L. Progress and Outlook ofSupercritical CO2-Heavy Oil Viscosity Reduction Technology: A Minireview[J]. Energy & Fuels, 2023, 37(16): 11567-11583.
[0015] [8] Yan K Y. Effect of supercritical CO2 treatment on rheological properties of crude oil with dissolved gas and its mechanism[D]. China University of Petroleum, 2017.
[0016] [9] Chen Haiyong, Su Weidong. Post-fracturing evaluation method of deep coal gas CO2 foam fracturing[J]. Drilling and Production Technology, 2024, 47(3): 97-101.
[0017]
[10] Cao X, Guo W, Zhu Q, et al. Supramolecular self-assembly ofrobust, ultra-stable, and high-temperature-resistant viscoelastic worm-likemicelles[J]. Journal of Colloid and Interface Science, 2023, 649: 403-415. Summary of the invention
[0018] The technical problem to be solved by the present invention is to overcome the defect of poor stability of CO2 foam in the prior art, and provide a micelle and foam containing the micelle. The micelle system in the present invention has good rheological properties, simple process, low preparation cost, and little environmental pollution. The foam system containing the micelle in the present invention has good stability and oil displacement efficiency, can realize the integration of fracturing and displacement, and significantly improves the recovery rate at high temperature, and the preparation operation steps are simple and the cost is low.
[0019] In the present invention, the inventors prepared a self-assembled worm-like micelle and a CO2 foam system containing the self-assembled worm-like micelle (for example, a supercritical CO2 foam system containing the self-assembled worm-like micelle) by precisely adjusting the ratio of surfactant to counterion, and also prepared a self-assembled worm-like micelle foam system combining nanoparticles with supercritical CO2.
[0020] The CO2 self-assembled worm-like micelle foam system (such as a supercritical CO2 self-assembled worm-like micelle foam system) in the present invention not only has low interfacial tension and high stability, but also has a suitable viscosity so that it can be effectively used as foam fracturing to form oil and gas reservoir fractures. In addition, this CO2 self-assembled worm-like micelle foam system can be quickly converted into an efficient oil displacement agent after the fracturing operation is completed, realizing a seamless connection between the fracturing and oil displacement processes.
[0021] Nano-silicon dioxide can also be added to the self-assembled worm-like micelles in the present invention. The addition of nano-silicon dioxide can significantly increase the viscosity, elasticity and stability of the foam, thereby further improving the plugging ability of the foam in the reservoir fractures, reducing gas cross-flow, and further improving the oil recovery efficiency.
[0022] The foam system containing self-assembled worm-like micelles (such as supercritical CO2 self-assembled worm-like micelle foam system) in the present invention is used for oil production, which can not only simplify the operation steps, reduce the overall cost, realize the integration of fracturing and displacement, but also effectively improve the recovery rate of oil and gas reservoirs. The present invention solves the above technical problems through the following technical solutions.
[0023] In a first aspect, the present invention provides a micelle comprising a cationic surfactant and a counter ion;
[0024] The mass ratio of the cationic surfactant to the counter ion is (3-6):1 or 8:1;
[0025] The cationic surfactant comprises an alkyl trimethyl ammonium salt; in the alkyl trimethyl ammonium salt, the number of carbon atoms in the alkyl carbon chain is ≥ 20;
[0026] The counter ion includes a salicylate ion;
[0027] In the micelle, the mass concentration of the cationic surfactant is 0.1wt%-1.0wt%.
[0028] In one embodiment of the present invention, the alkyltrimethylammonium salt is alkyltrimethylammonium bromide or alkyltrimethylammonium chloride.
[0029] In a preferred embodiment of the present invention, in the alkyl trimethylammonium salt, the number of carbon atoms in the alkyl carbon chain is 20-25, for example 22.
[0030] In a preferred embodiment of the present invention, the alkyltrimethylammonium salt is selected from behenyltrimethylammonium salt, such as behenyltrimethylammonium chloride.
[0031] In one embodiment of the present invention, the cationic surfactant further comprises hexadecyltrimethylammonium salt, such as hexadecyltrimethylammonium bromide.
[0032] In one embodiment of the present invention, the micelle may further include a zwitterionic surfactant, such as cocamidopropyl betaine.
[0033] In a preferred embodiment of the present invention, the salicylate ion (C7H5O3 - ) is the salicylic acid ion in the form of sodium salicylate.
[0034] In one embodiment of the present invention, the counter ion further comprises a p-toluenesulfonate ion, for example, a p-toluenesulfonate ion in the form of sodium p-toluenesulfonate.
[0035] In one embodiment of the present invention, the counter ion further comprises a halogen ion. In the present invention, the halogen ion is generally a fluoride ion, a chloride ion, a bromide ion or an iodide ion.
[0036] In one embodiment of the present invention, among the counterions, the halogen ions are iodide ions, for example, iodide ions in the form of sodium iodide.
[0037] In a preferred embodiment of the present invention, the mass ratio of the cationic surfactant to the counter ion is (3-5):1 or 8:1, for example 4:1.
[0038] In a preferred embodiment of the present invention, the mass ratio of the cationic surfactant to the counter ion is 3:1, 4:1, 5:1, 6:1, or 8:1.
[0039] In the present invention, the micelle is a solution rich in surfactant.
[0040] In a preferred embodiment of the present invention, in the micelle, the mass concentration of the cationic surfactant is 0.1wt%-0.5wt%, for example, 0.3wt%.
[0041] In one embodiment of the present invention, in the micelle, the mass concentration of the counter ion is 0.0375 wt% or 0.05wt%-2.0wt%, such as 0.05wt%-0.1wt%, and also such as 0.1 wt%, 0.075 wt%, 0.06 wt% or 0.05 wt%.
[0042] In one embodiment of the present invention, the micelle further comprises one or more of a proppant, a fluid loss reducer, and a breaker.
[0043] Wherein, the proppant can be used to enhance the sand carrying capacity and supporting strength of the foam system.
[0044] Wherein, the proppant may be ceramsite, and the particle size of the ceramsite may be 20-40 meshes.
[0045] Wherein, in the micelle, the mass concentration of the proppant may be 0.5-1.0 wt%, such as 0.5 wt%, 0.75 wt% or 1.0 wt%.
[0046] The fluid loss reducer can be used to reduce the fluid loss rate of the fracturing fluid and maintain the stability of the system.
[0047] Wherein, the fluid loss reducer may be carboxymethyl cellulose (CMC), and the weight average molecular weight of the carboxymethyl cellulose may be 500-2000.
[0048] Wherein, in the micelle, the mass concentration of the fluid loss reducer may be 0.1-1.0 wt%, for example, 0.5 wt%.
[0049] The debonding agent can be used to destroy the foam structure after the fracturing operation is completed, so as to facilitate subsequent operations.
[0050] Wherein, the degumming agent may be ammonium persulfate.
[0051] Wherein, in the micelle, the mass concentration of the fluid loss reducer may be 0.01-0.1 wt%, for example, 0.05 wt%.
[0052] In a preferred embodiment of the present invention, the micelle further comprises nano-silicon dioxide. Nano-silicon dioxide has the surface properties of high specific surface area and rich hydroxyl groups, which can play an enhanced interface role.
[0053] In a preferred embodiment of the present invention, in the micelle, the mass concentration of the silicon dioxide is 0wt%-1.0wt%, preferably 0.1wt%-1.0wt%, such as 0.1wt%-0.5wt%, and also such as 0.5wt%.
[0054] In one embodiment of the present invention, the particle diameter of the nano-silicon dioxide is 10-20 nm, for example, 15 nm.
[0055] In one embodiment of the present invention, the micelle includes 0.1wt%-1.0wt% of surfactant behenyltrimethylammonium chloride, counterion sodium salicylate, 0.1wt%-1.0wt% of nano-silica, and the remaining component is water.
[0056] In one embodiment of the present invention, the micelle includes 0.3 wt % of surfactant behenyltrimethylammonium chloride, 0.075 wt % of counterion sodium salicylate, and 0.5 wt % of nano-silicon dioxide.
[0057] In a second aspect, the present invention also provides a method for preparing the micelle, which comprises the following steps:
[0058] The cationic surfactant and the counter ion are dissolved in a solvent to obtain the product;
[0059] When the micelle further includes one or more of the proppant, the fluid loss agent, and the breaker: the cationic surfactant and the counter ion are dissolved and mixed with one or more of the proppant, the fluid loss agent, and the breaker to obtain the micelle;
[0060] When the micelle also includes the nano-silicon dioxide, the cationic surfactant and the counter ion are dissolved and mixed with the nano-silicon dioxide to obtain the micelle.
[0061] In one embodiment of the present invention, the solvent is water, such as deionized water.
[0062] In one embodiment of the present invention, the dissolving temperature is 50-70°C, for example, 60°C.
[0063] In one embodiment of the present invention, the nano-silica is dispersed in the micelles by ultrasound.
[0064] In one embodiment of the present invention, the ultrasonication time is 5-20 min, for example, 10 min.
[0065] In a third aspect, the present invention also provides a CO2 micellar foam, which comprises CO2 and the micelles as described above.
[0066] In one embodiment of the present invention, the amount of CO2 introduced is such that the pressure reaches 10-15 MPa, for example, 12 MPa.
[0067] In one embodiment of the present invention, the CO2 exists in the form of supercritical CO2.
[0068] In one embodiment of the present invention, the CO2 exists in the form of non-supercritical CO2.
[0069] In the art, the supercritical temperature of CO2 is 31.06° C. In the supercritical state, the density of CO2 decreases, the boiling point increases, and the solubility increases.
[0070] In a fourth aspect, the present invention also provides a method for preparing the CO2 micellar foam, which comprises the following steps:
[0071] The method is prepared by mixing and emulsifying CO2 and the micelles.
[0072] In one embodiment of the present invention, the amount of CO2 introduced is such that the pressure reaches 10-15 MPa, for example, 12 MPa.
[0073] In one embodiment of the present invention, the emulsification temperature is 50-70°C, for example, 60°C.
[0074] In one embodiment of the present invention, the emulsification pressure is 10-15 MPa, for example 12 MPa.
[0075] In one embodiment of the present invention, the emulsification time is 30-100 min, for example 60 min.
[0076] In a fifth aspect, the present invention also provides an application of the CO2 micellar foam as a fracturing fluid and / or displacement fluid in oil production.
[0077] On the basis of being in accordance with the common sense in the art, the above-mentioned preferred conditions can be arbitrarily combined to obtain the preferred embodiments of the present invention.
[0078] The reagents and raw materials used in the present invention are commercially available.
[0079] The positive and progressive effects of the present invention are:
[0080] (1) The micelle system of the present invention has good rheological properties, simple process, low preparation cost and little environmental pollution. At the same time, the micelle-containing foam system of the present invention (such as the micelle-containing supercritical CO2 foam system) has high stability, rheological properties and viscosity at high temperatures, effectively improving the oil recovery rate, ensuring the reliability, repeatability and effectiveness of the technology, and providing reliable technical guarantee for oil field application.
[0081] (2) The self-assembled worm-like micelle foam system of nano-silica combined with supercritical CO2 in the present invention can be applied to the integrated fracturing and displacement technology in oil production, which can significantly improve the oil recovery rate; the system cleverly combines the unique physical properties of supercritical CO2 and the interfacial activity of nano-silica to form a foam system with good stability, realizing the simultaneous fracturing and oil displacement, reducing the operation steps and reducing costs. Experiments show that the self-assembled worm-like micelle foam system of nano-silica combined with supercritical CO2 in the present invention has a significant effect in improving oil recovery, especially in medium and high temperature reservoirs.
[0082] Specifically, the supercritical CO2 self-assembled worm-like micelle foam system of the present invention has the following advantages:
[0083] 1) Improved oil recovery: Core experiments have shown that the oil recovery rate of the foam system of the present invention at 60°C reaches 91%, which is nearly twice as high as that of conventional water flooding technology, significantly improving the oil recovery rate of the reservoir.
[0084] It is particularly suitable for medium and high temperature reservoir conditions, can maintain stability under these conditions, and effectively improve the recovery rate.
[0085] 2) Reduce costs: Reduce the use of chemical additives and expensive chemical additives. The integrated fracturing displacement technology simplifies the operation process, reduces the operation steps, reduces manpower and time costs, improves operation efficiency and reduces the overall cost of tertiary oil recovery.
[0086] 3) Environmentally friendly: Compared with traditional fracturing technology, the foam system of the present invention reduces the impact on the reservoir environment and reduces the risk of environmental pollution. The raw materials and methods used in this technology comply with current environmental regulations and requirements and are a green oil recovery technology.
[0087] 4) Strong adaptability: The foam system can adapt to the conditions of the reservoir at different temperatures, especially showing better stability at 60°C. The foam system prepared under 12MPa CO2 pressure can simulate the high-pressure environment in the reservoir, ensuring stability and effectiveness in practical applications.
[0088] 5) Improved temperature resistance: The addition of nano-silica significantly improves the temperature resistance of the foam system, and it can still maintain stability in an environment up to 100°C. The high thermal stability of nano-silica helps the application of the foam system in high-temperature reservoir conditions and reduces the risk of thermal decomposition or thermal relaxation.
[0089] 6) Experimental verification: The core displacement experiment verified the high-efficiency oil recovery performance of the foam system, ensuring the reliability and effectiveness of the technology. The consistency and repeatability of the experimental results proved the stability and repeatability of the technology, providing reliable technical support for oil field applications. DETAILED DESCRIPTION
[0090] The present invention is further described below by way of examples, but the present invention is not limited to the scope of the examples. The experimental methods in the following examples without specifying specific conditions are carried out according to conventional methods and conditions, or selected according to the product specifications.
[0091] In the following examples and comparative examples, the raw material related information is as follows:
[0092] Behenyltrimethylammonium chloride (DCTAC): chemical formula is C 25 H 54 ClN, CAS number is 17301-53-0;
[0093] Hexadecyltrimethylammonium chloride: Chemical formula C 19 H 42 ClN, CAS number is 112-02-7;
[0094] Cocamidopropyl Betaine: Molecular Formula C 19 H 38N2O3, CAS number is 61789-40-0;
[0095] Sodium salicylate (NaSaL): The chemical formula is , CAS number is 54-21-7, purity is 99%;
[0096] Sodium 3-hydroxynaphthalene-2-carboxylate (SHNC), chemical formula is ;
[0097] p-Toluenesulfonic acid: , CAS number is 104-15-4;
[0098] Nano-silicon dioxide: purity: 99.5%, particle diameter 15nm;
[0099] Ceramsite was purchased from: particle size 20-40 mesh;
[0100] Carboxymethyl cellulose (CMC): weight average molecular weight between 500 and 2000.
[0101] Example 1: Self-assembly of worm-like micelles at room temperature
[0102] The specific preparation steps are as follows:
[0103] Preparation of worm-like micelle system: Prepare surfactant behenyltrimethylammonium chloride (DCTAC) and counterion sodium salicylate (NaSaL) and dissolve them in deionized water according to the concentrations shown in Table 1. Heat and stir at 60°C to ensure complete dissolution to form worm-like micelles.
[0104] Table 1
[0105]
[0106] Effect Example 1
[0107] The worm-like micelle solution in Example 1 was subjected to a steady-state shear test using a HAAKE MARS 60 rheometer, with the shear rate set from 0.001 s -1 Up to 1000s -1 , select a system that meets the requirements of good rheological properties and low concentration. The specific shear viscosity is shown in Table 2 below.
[0108] Table 2
[0109]
[0110] Based on Table 2 above, it can be seen that when the mass ratio of surfactant docosyltrimethylammonium chloride (DCTAC) and counterion sodium salicylate (NaSaL) is 4:1, the micelle shear viscosity is the highest and the stability is the best.
[0111] The structure of the worm-like micelle system in Examples 1-4 is as follows: the long hydrophobic tails of DCTAC gather together to form the hydrophobic core of the micelle. In this core, the hydrophobic tails are closely arranged to reduce contact with water. The hydrophilic carboxylate groups in the NaSaL molecules interact with water, while the hydrophobic benzene rings are inserted into the hydrophobic core of the DCTAC micelles and interact with the hydrophobic tails on the surface of the micelles through π-π interactions and hydrogen bonds.
[0112] Example 2
[0113] Optimization of fracturing fluid: Mix the stable foam system with fracturing fluid additives, including the appropriate amount of proppant, fluid loss reducer and debonder. Determine the optimal amount of additives to adjust the viscosity and sand carrying capacity of the fracturing fluid based on the expected width and length of the reservoir fractures.
[0114] Steps:
[0115] (1) Preparation of micellar system
[0116] First, 0.3 wt% of docosyltrimethylammonium chloride (DCTAC, 0.3 g) and 0.075 wt% of sodium salicylate (NaSaL, 0.075 g) were dissolved in 100 mL of deionized water and stirred evenly to form a worm-like micelle solution.
[0117] (2) Mixing of additives
[0118] Proppant: Add 0.5-1.0 g of proppant (ceramsite) at a ratio of 5-10 g / L to enhance the sand carrying capacity and support strength of the foam system.
[0119] Fluid loss reducer: Add 0.5 wt% carboxymethyl cellulose (CMC), i.e. 0.5 g, to reduce the fluid loss rate of the fracturing fluid and maintain the stability of the system.
[0120] Debonding agent: Add 0.05 wt% ammonium persulfate, i.e. 0.05 g, to destroy the foam structure after the fracturing operation to facilitate subsequent operations.
[0121] (3) Solution sampling
[0122] Take 6.75 mL from the mixed 100 mL solution and place it in a 22.5 mL high-pressure reactor to ensure that all additives are evenly distributed in the system.
[0123] (4) Carbon dioxide introduction and foam formation
[0124] After the reactor was sealed, 12 MPa of carbon dioxide was introduced and stirred at 60°C for 60 minutes to form a stable CO2 foam system.
[0125] The amount of additives is calculated as shown in Table 3 below.
[0126] Table 3
[0127]
[0128] Example 2-1: In 100 mL of worm-like micelle solution: the added mass of proppant (ceramsite) is 0.5 g, the added mass of filtrate reducer (CMC) is 0.5 g, and the added mass of breaker (ammonium persulfate) is 0.05 g.
[0129] Example 2-2: In 100 mL of worm-like micelle solution: the added mass of proppant (ceramsite) is 0.75 g, the added mass of filtrate reducer (CMC) is 0.5 g, and the added mass of breaker (ammonium persulfate) is 0.05 g.
[0130] Example 2-3: In 100 mL of worm-like micelle solution: the added mass of proppant (ceramsite) is 1.0 g, the added mass of filtrate reducer (CMC) is 0.5 g, and the added mass of breaker (ammonium persulfate) is 0.05 g.
[0131] Effect Example 2
[0132] (1) The viscosity, sand carrying capacity and filtration rate of the foam system were tested at different proppant addition amounts. The results are shown in Table 4 below.
[0133] Test method for viscosity of foam system:
[0134] Use a rotational viscometer (such as Brookfield DV-II) to test the viscosity of the foam system. Place the foam system in a constant temperature water bath and control the test temperature to 25°C. Select an appropriate rotor and speed, and record the viscosity value in the steady state in mPa·s.
[0135] Test method for sand carrying capacity of foam system:
[0136] The foam system and a certain amount of sand are mixed and placed in a transparent container to simulate the flow state under fracturing conditions. The uniform suspension capacity of the sand particles in the system is observed and recorded, and the mass of sand particles that can be carried per unit foam volume (g / m³) is calculated to ensure that the sand particles are evenly distributed and do not settle during the entire test process.
[0137] Test method for filtration rate of foam system:
[0138] The test is conducted using a filter loss test device (API filter loss instrument). The foam system is placed in a filter loss cup, a constant pressure (e.g. 0.7 MPa) is applied above, and the volume of liquid filtered out per unit time is recorded in mL / min. The temperature is kept constant throughout the test, and standard filter paper (e.g. 100 mesh) is used to simulate the formation pore conditions.
[0139] Table 4
[0140]
[0141] in conclusion:
[0142] The experiment shows that with the increase of proppant content, the viscosity and sand carrying capacity of the foam system significantly increase, while the filtration rate gradually decreases. When the proppant addition amount is 1.0 g, the viscosity of the foam system reaches 55 mPa·s, the sand carrying capacity reaches 220 g / m³, and the filtration rate is 0.3 mL / min, showing good fracturing performance.
[0143] (2) Use of foam system for fracturing: Before fracturing, the foam system in Examples 2-1, 2-2, and 2-3 is injected into the fracturing equipment. The foam system is injected into the cracks of the oil and gas reservoir by a high-pressure pump, and the high viscosity and elastic properties of the foam system are utilized to form an effective plug in the cracks, thereby increasing the crack network and permeability of the oil and gas reservoir. The stability of the foam system in the cracks helps to maintain the open state of the cracks, creating favorable conditions for subsequent oil recovery operations.
[0144] Example 3
[0145] Preparation of self-assembled worm-like micelles in supercritical CO2 foam:
[0146] The worm-like micelle solution in Example 1 was placed in a high-pressure emulsification kettle, CO2 was introduced to a pressure of 12 MPa, and stirred for 60 minutes to form a stable CO2 foam system.
[0147] The supercritical temperature of CO2 is 31.06°C. In the supercritical state, the density of CO2 decreases, the boiling point increases, and the solubility increases.
[0148] The compositions of each embodiment are shown in Table 5.
[0149] Table 5
[0150]
[0151] Effect Example 3
[0152] (1) Foam stability test: The self-assembled worm-like micelle supercritical CO2 foam (the mass ratio of DCTAC and NaSaL is 4:1) in Example 3-4 was taken to observe the morphology and stability of the foam system at different time points such as 0 hour, 4 hours, 8 hours, and 12 hours.
[0153] The average foam diameter is used to characterize the foam. The larger the diameter, the greater the foam coarsening and the worse the stability. Table 6 below shows the average foam diameter (μm) at different temperatures and time h.
[0154] Table 6
[0155]
[0156] (2) Foam flooding experiments were conducted at room temperature (25°C) using an artificial core with a permeability of 490 mD:
[0157] Under simulated reservoir conditions (15 MPa confining pressure and 12 MPa back pressure), the foam displacement agent in Example 3-4 (the mass ratio of DCTAC to NaSaL is 4:1) was injected at a rate of 1 mL / min using a Quizix pump. The oil production at different time periods was recorded, and the recovery factor was calculated. The higher the recovery factor, the higher the oil recovery efficiency. The specific data are shown in Table 7 below.
[0158] Table 7
[0159]
[0160] Results: Under normal temperature conditions, the foam system showed good stability and oil recovery efficiency, with a recovery factor of 78%, which was significantly higher than the 54% of water drive under the same conditions.
[0161] (3) Foam flooding experiment was carried out at 60°C using an artificial core with a permeability of 490 mD:
[0162] The foam system in Example 3-4 (the mass ratio of DCTAC to NaSaL is 4:1) was used, and the foam system was stabilized at 60° C. for a corresponding time to keep the system temperature uniform.
[0163] At 60°C, an artificial core with a permeability of 490 mD was used for foam displacement experiments. Under simulated reservoir conditions (15 MPa confining pressure and 12 MPa back pressure), a Quizix pump was used to inject foam displacement agent at a rate of 1 mL / min, and the oil production at different time periods was recorded. The specific data are shown in Table 8 below.
[0164] Table 8
[0165]
[0166] Results: At 60°C, the recovery factor of the foam system reached 91%, indicating that the foam system has excellent oil displacement performance under medium temperature conditions.
[0167] (4) Foam flooding experiment was carried out at 80°C using an artificial core with a permeability of 490 mD:
[0168] The same foam system as in Example 3-4 (the mass ratio of DCTAC to NaSaL is 4:1) was used, and the foam system was maintained at 80° C. for a corresponding period of time to ensure that the system temperature was uniform.
[0169] The foam displacement experiment was conducted at 80°C using an artificial core with a permeability of 490 mD. Under simulated reservoir conditions (15 MPa confining pressure and 12 MPa back pressure), the foam displacement agent was injected at a rate of 1 mL / min using a Quizix pump, and the oil production at different time periods was recorded. The specific data are shown in Table 9 below.
[0170] Table 9
[0171]
[0172] Results: At 80°C, the recovery factor of the foam system was 80%, indicating that the stability and oil displacement efficiency of the foam system were adversely affected under high temperature conditions.
[0173] (5) Foam flooding experiment at 100°C using an artificial core with a permeability of 490 mD:
[0174] The same foam system as in Example 3-4 (the mass ratio of DCTAC to NaSaL is 4:1) was used, and the foam system was maintained at 100° C. for a corresponding period of time to ensure that the system temperature was uniform.
[0175] At 100°C, an artificial core with a permeability of 490 mD was used for foam displacement experiments. Under simulated reservoir conditions (15 MPa confining pressure and 12 MPa back pressure), a Quizix pump was used to inject foam displacement agent at a rate of 1 mL / min, and the oil production at different time periods was recorded. The specific data are shown in Table 10 below.
[0176] Table 10
[0177]
[0178] (6) Take the self-assembled worm-like micelle supercritical CO2 foam in Example 3 and compare the foam volume at 40°C and 0h.
[0179] Example 3-1, Example 3-2, and Example 3-7 were unable to form stable foam.
[0180] Example 3-3, Example 3-4, Example 3-5, Example 3-6, and Example 3-8 can form stable foam, and Example 3-4 forms the largest amount of foam.
[0181] Example 4
[0182] Preparation of Nanoparticle Cooperative Self-Assembled Worm-Like Micelles in Supercritical CO2 Foam:
[0183] 0.5 wt % of nano-silica was added to the worm-like micelle solution (the mass ratio of DCTAC to NaSaL was 4:1) in Example 1-4 to obtain a mixed solution, which was treated with ultrasound for 10 minutes to ensure uniform dispersion.
[0184] The mixed liquid was placed in a high-pressure emulsification kettle, CO2 was introduced to a pressure of 12 MPa, and stirred for 60 minutes to form a stable CO2 foam system.
[0185] Effect Example 4
[0186] (1) Recovery efficiency of supercritical CO2 foam flooding by 80℃ nanoparticle-assisted self-assembly of worm-like micelles
[0187] The same foam system as in Example 4 was used, and the foam system was kept at 80°C for a period of time to ensure that the system temperature was uniform.
[0188] The foam displacement experiment was conducted at 80°C using an artificial core with a permeability of 490 mD. Under simulated reservoir conditions (15 MPa confining pressure and 12 MPa back pressure), the foam displacement agent was injected at a rate of 1 mL / min using a Quizix pump, and the oil production at different time periods was recorded. The specific data are shown in Table 11 below.
[0189] Table 11
[0190]
[0191] Results: At 80°C, the recovery rate of the foam system with the introduction of nano-silica reached 90%, indicating that the synergistic effect of nano-silica helps to improve the temperature resistance and oil displacement performance of the foam system.
[0192] (2) Recovery efficiency of supercritical CO2 foam flooding by 100℃ nanoparticle-assisted self-assembly of worm-like micelles
[0193] The foam system in Example 4 was used and the foam system was kept at 100° C. for a period of time to ensure that the system temperature was uniform.
[0194] At 100°C, an artificial core with a permeability of 490 mD was used for foam displacement experiments. Under simulated reservoir conditions (15 MPa confining pressure and 12 MPa back pressure), a Quizix pump was used to inject foam displacement agent at a rate of 1 mL / min, and the oil production at different time periods was recorded. The specific data are shown in Table 12 below.
[0195] Table 12
[0196]
[0197] Results: At 100°C, the recovery rate of the foam system with the introduction of nano-silica reached 85%, indicating that the foam system can maintain a certain stability and oil displacement efficiency even under extremely high temperature conditions.
[0198] Comparing the stability test results of the foam systems of Examples 3-4 and Example 4 at different temperatures, it can be seen that the foam system without nanoparticles in Examples 3-4 is preferably used at 60° C., and the foam system with nanoparticles in Example 4 has a temperature resistance of 100° C. The foam system in Example 4 shows better stability at higher temperatures and is more suitable for simulating medium and high temperature conditions in oil reservoirs.
[0199] Comparative Example 1
[0200] Dodecyltrimethylammonium chloride (DCTAC) and counterion sodium 3-hydroxynaphthalene-2-carboxylate (SHNC) were dissolved in deionized water at a molar ratio of 2:1, and the mass concentration of dodecyltrimethylammonium chloride (DCTAC) was 0.3 wt%; heated and stirred at 60°C to ensure complete dissolution, forming worm-like micelles. The self-assembled worm-like micelle system was placed in a high-pressure emulsification reactor, carbon dioxide was introduced to a pressure of 12MPa, and stirred for 60 minutes, but no stable CO2 foam could be formed.
[0201] Comparative Example 2
[0202] The surfactant dodecyltrimethylammonium chloride (DCTAC) and the counterion sodium 3-hydroxynaphthalene-2-carboxylate (SHNC) were dissolved in deionized water at a molar ratio of 2:1, and the mass concentration of dodecyltrimethylammonium chloride (DCTAC) was 1.2 wt% (30mM); heated and stirred at 60°C to ensure complete dissolution to form worm-like micelles. The self-assembled worm-like micelle system was placed in a high-pressure emulsification reactor, carbon dioxide was introduced to a pressure of 12MPa, and stirred for 60 minutes, but no stable CO2 foam could be formed.
[0203] Comparative Example 3
[0204] The surfactant hexadecyltrimethylammonium chloride and the counterion p-toluenesulfonate ion were dissolved in deionized water in a mass ratio of 4:1 with mass concentrations of 0.3 wt% and 0.075 wt%, respectively. The mixture was heated and stirred at 60°C to ensure complete dissolution. Apparently, no gel state appeared and a self-assembled worm-like micelle system could not be formed.
[0205] Comparative Example 4
[0206] Dodecyltrimethylammonium chloride (DCTAC) and counterion p-toluenesulfonate ion were dissolved in deionized water in a mass ratio of 4:1, with mass concentrations of 0.3 wt% and 0.075 wt%, respectively. The mixture was heated and stirred at 60°C to ensure complete dissolution. Apparently, no gel state appeared and a self-assembled worm-like micelle system could not be formed.
[0207] Comparative Example 5
[0208] Cocamidopropyl betaine and counter ion p-toluenesulfonate ion were dissolved in deionized water in a mass ratio of 4:1 with mass concentrations of 0.3 wt % and 0.075 wt %, respectively. The mixture was heated and stirred at 60°C to ensure complete dissolution. Apparently, no gel state appeared and a self-assembled worm-like micelle system could not be formed.
Claims
1. A micelle, characterized in that It includes a cationic surfactant and a counterion; The mass ratio of the cationic surfactant to the counter ion is (3-6):1 or 8:1; The cationic surfactant comprises an alkyl trimethyl ammonium salt; in the alkyl trimethyl ammonium salt, the number of carbon atoms in the alkyl carbon chain is ≥ 20; The counter ion includes a salicylate ion; In the micelle, the mass concentration of the cationic surfactant is 0.1wt%-1.0wt%.
2. The micelle according to claim 1, characterized in that The alkyltrimethylammonium salt is alkyltrimethylammonium bromide or alkyltrimethylammonium chloride; And / or, in the alkyl trimethylammonium salt, the number of carbon atoms in the alkyl carbon chain is 20-25, for example 22.
3. The micelle according to claim 1, characterized in that The micelles satisfy one or more of the following conditions: (1) The alkyl trimethyl ammonium salt is selected from behenyl trimethyl ammonium salts, such as behenyl trimethyl ammonium chloride; (2) The cationic surfactant also includes hexadecyltrimethylammonium salts, such as hexadecyltrimethylammonium bromide; (3) The micelles also include a zwitterionic surfactant, such as cocamidopropyl betaine; (4) The salicylic acid ion is a salicylic acid ion in the form of sodium salicylate; (5) The counter ions further include p-toluenesulfonate ions and / or halogen ions.
4. The micelle according to any one of claims 1 to 3, characterized in that The micelles satisfy one or more of the following conditions: (6) The mass ratio of the cationic surfactant to the counterion is (3-5):1 or 8:1, for example 4:1; (7) In the micelle, the mass concentration of the cationic surfactant is 0.1wt%-0.5wt%, for example, 0.3wt%; (8) In the micelle, the mass concentration of the counter ion is 0.0375 wt% or 0.05 wt%-2.0 wt%, such as 0.05 wt%-0.1 wt%, and also such as 0.1 wt%, 0.075 wt%, 0.06 wt% or 0.05 wt%.
5. The micelle according to claim 1, characterized in that The micelle also includes one or more of a proppant, a fluid loss reducer, and a gel breaker; And / or, the micelle further includes nano-silicon dioxide.
6. The micelle according to claim 5, characterized in that The micelles satisfy one or more of the following conditions: (9) The proppant is ceramsite, and the particle size of the ceramsite may be 20-40 mesh; (10) In the micelle, the mass concentration of the proppant is 0.5-1.0 wt%, such as 0.5 wt%, 0.75 wt% or 1.0 wt%; (11) The fluid loss reducer is carboxymethyl cellulose; the weight average molecular weight of the carboxymethyl cellulose may be 500-2000; (12) In the micelle, the mass concentration of the fluid loss reducer is 0.1-1.0 wt%, for example, 0.5 wt%; (13) The debonding agent is ammonium persulfate; (14) The mass concentration of the fluid loss reducer is 0.01-0.1 wt%, for example, 0.05 wt%; (15) The particle diameter of the nano-silicon dioxide is 10-20 nm, for example, 15 nm.
7. A method for preparing a micelle as claimed in any one of claims 1 to 6, characterized in that: It includes the following steps: The cationic surfactant and the counter ion are dissolved in a solvent to obtain the product; When the micelle further includes one or more of the proppant, the fluid loss agent, and the breaker: the cationic surfactant and the counter ion are dissolved and mixed with one or more of the proppant, the fluid loss agent, and the breaker to obtain the micelle; When the micelle also includes the nano-silicon dioxide, the cationic surfactant and the counter ion are dissolved and mixed with the nano-silicon dioxide to obtain the micelle.
8. A CO2 micellar foam, characterized in that: It comprises CO2 and the micelle as described in any one of claims 1-6.
9. A method for preparing CO2 micellar foam as claimed in claim 8, characterized in that: It includes the following steps: The mixture is prepared by mixing and emulsifying CO2 and the micelle according to any one of claims 1 to 6; The amount of CO2 introduced can be such that the pressure reaches 10-15 MPa, for example 12 MPa; The emulsification temperature may be 50-70°C, for example 60°C; The emulsification pressure may be 10-15 MPa, for example 12 MPa; The emulsification time may be 30-100 min, for example 60 min.
10. Use of the CO2 micellar foam as claimed in claim 8 as a fracturing fluid and / or displacement fluid in oil production.